PARTISIPASI MASYARAKAT DALAM PEMANFAATAN HUTAN MANGROVE DI SIDANGOLI - Muin, Fadlan (Green Earth, 2012)
Mangroves are very important in coastal resource management. The most important function of mangroves for coastal areas is the link between land and sea. Plants, animals, other objects, and plant nutrients are transferred to the mainland or to the sea through mangrove. Mangroves act as a filter to reduce the adverse effects of major environmental change, and as a food source for marine (coastal) and terrestrial biota. The relationship between the region means that biodiversity around mangroves should also be considered, so that the total biodiversity of ecosystems is higher. Beside that economic potential of mangroves in Sidangoli can earn from three main sources namely forest, estuarine and coastal fisheries (shallow water), as well as natural attractions. Because of population pressure, especially coastal areas Sidangoli, resulting in a change in land use and utilization of natural resources in excess, if not protected by mangrove forests quickly become thinner and broken in the coastal Sidangoli. The need to balance must be achieved between meeting the needs now for economic development at a party, and conservation of environmental support systems on the other. Growing awareness of the protection function, the productive and socio-economic impacts of mangrove ecosystems in the tropics, and due to the decreasing availability of natural resources, encourage the lifting of the problem needs conservation and sustainability of the integrated management of resources-such valuable resources. Given the potential for multi-use natural resources, it is imperative that the management of mangrove forests based on terrestrial and aquatic ecosystems, in relation to integrated coastal zone management plan.